Psychometric properties of decision to study abroad attributes among international edu-tourists from emerging economies - Ojo, Bello Yekinni; Raja Yusof, Raja Nerina (International Organization of Scientific Research, 2017)
This article developed and validates the psychometric properties of attributes that influences edu-tourists from emerging economies to study in emerging country (AISE) in respect to Malaysia. A survey was done on 1000 international edu-tourists from Africa, Asia and Middle-East in 13 Malaysian edu-tourism institutions. The structure of the underlying dimensions of decision to study abroad was framed based on the Push and Pull theory and literature. Reliability analysis, exploratory, and confirmatory factor analysis were applied to investigate internal consistency and construct validity of the AISE model using SPSS and Analysis of Moment Structure version 22. The Composite Reliability (CR) and Average Variance Extracted (AVE) were examined to determine the construct reliability and convergent validity. Result of exploratory factor analysis showed that four dimensions emerged with 20 corresponding items. The confirmatory factor analysis confirmed a three-dimensional model with14 corresponding indicators of a good fit. Dimensions in the final model include: Social-cultural factor, Economic factor, and Career development with valid Cronbach’s Alpha values and a good construct reliability. The value of the AVE shows that the AISE model has adequate convergent validity. Since the focus of the Malaysian government is to attract 200, 000 international edu-tourists by the year 2020. Factors capable of determining international edu-tourists from other emerging countries to decide to study abroad in Malaysia need to be identified. This study suggests a three-dimensional AISE model capable of explaining the decision to study abroad behaviour of international edu-tourists from emerging economies.